Awareness of the threats of sexually transmitted diseases among youth - review of studies - Irena Puszkarz (Kazimierz Wielki University, 2018)
Background: Increasing problem of sexually transmitted diseases needs a well-organized effort allowing preserving and strengthening sexual health. Proper knowledge about sexually transmitted diseases (STD) allows not only to protect oneself against contagion but also others. Incorrect information in that field may give false sense of security and in consequence increase in STD rates. Appropriate sources of knowledge are inherent in awareness-raising and taking mature actions. Seeking effective methods of transferring knowledge and awareness-raising about STD is the subject of actions of many professionals. Objective: Analysis of chosen scientific work concerning the level of knowledge and the awareness of the threats of sexually transmitted diseases among Polish youth. Material & methods: The basis for this paper was the review of articles and scientific work in Polish magazines that were the results of studies of the awareness of the threats of STD among youth. Papers of high quality of presented studies and with interesting results were selected for analysis. Results: Analyzed studies were using questionnaires created by authors and containing questions dealing with knowledge about etiological factors, symptoms and risky behaviour leading to STD infection. The results of the studies confirmed significant yet in some aspects selective and limited knowledge of the subjects about threats and prevention of STD. The youth knew few diseases, did not realize STD were asymptomatic, and often did not notice the risk of infection caused by early sexual initiation and having many sexual partners. Women and residents of urban areas knew more about STD than men and residents of rural areas. Conclusion: Selective and not well-organized knowledge limits possibility of eliminating hazardous behaviour contributing to transferring STD. The lack of understanding of the threat and asymptomatic course of STD leads to unaware carriage of STD and, in consequence to spreading the diseases and their complications. Observed decrease of the age of sexual initiation requires to introduce effective prevention based on coordination of the actions of young man or woman, their surroundings and educational units. It is necessary to complement school educational programmes by regularly repeated information about etiology, clinical picture of reproductive system diseases, paying particular attention to early detection of cancer and STD prevention.